2016
DOI: 10.33549/physiolres.933271
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity in Children and Adolescents: Physiology, Hypertension, Obesity, Diabetes Mellitus

Abstract: The increased prevalence of obesity in children and its complications have led to a greater interest in studying baroreflex sensitivity (BRS) in children. This review of BRS in children and adolescents includes subtopics on: 1. Resting values of BRS and their reproducibility, 2. Genetics of BRS, 3. The role of a primarily low BRS and obesity in the development of hypertension, and 4. Association of diabetes mellitus, BRS, and obesity. The conclusions specific to this age follow from this review: 1. The mean he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…However, both the decrease in BRS and the increase in LF/HF ratio from supine to upright were significantly greater in pediatric patients with OHT than those in controls. The reduction of BRS is associated with the sympathetic activation (17,26,27), and the increased LF/HF ratio indicates an obvious sympathetic predominance. Therefore, the significant drop of BRS and the remarkably increased LF/HF ratio at standing in the OHT patients demonstrated sympathetic overactivity in adolescents with OHT when upright.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both the decrease in BRS and the increase in LF/HF ratio from supine to upright were significantly greater in pediatric patients with OHT than those in controls. The reduction of BRS is associated with the sympathetic activation (17,26,27), and the increased LF/HF ratio indicates an obvious sympathetic predominance. Therefore, the significant drop of BRS and the remarkably increased LF/HF ratio at standing in the OHT patients demonstrated sympathetic overactivity in adolescents with OHT when upright.…”
Section: Discussionmentioning
confidence: 99%
“…Baroreflex is essential in the instant regulation of BP (24,25), and LF/HF ratio reflects the predominant component among sympathetic and vagal tone (18). Normally, BRS and RRI variability decrease but LF/HF ratio increases after standing (17,18,26). However, both the decrease in BRS and the increase in LF/HF ratio from supine to upright were significantly greater in pediatric patients with OHT than those in controls.…”
Section: Discussionmentioning
confidence: 99%
“…This is very important to know, because decreased small bowel resorption is a concomitant phenomenon of several diseases and common postoperative consequence. On the other hand, it is also well known that European populations are today affected by several civilization diseases, including overweight and obesity (Doak et al 2012, Honzikova andZavodna 2016). Thus, additional knowledge about the effects of individual food additives on the duodenal morphology is necessary and may result in practical output for dietetic indication and preparation of better nutritional products.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no significant differences in the HF power of HRV were observed in other studies between young obese subjects and healthy age-and gendermatched controls (Paschoal et al, 2009;Vanderlei et al, 2010;Javorka et al, 2016). Previous studies also demonstrated an impairment of arterial baroreflex (lower baroreflex sensitivity expressed as heart rate changes related to arterial blood pressure change) in obese children and adolescents, illustrating an impairment of reflex parasympathetic control (Honzikova et al, 2006;Krontoradova et al, 2008;Lazarova et al, 2009;Honzikova and Zavodna, 2016).…”
Section: Introductionmentioning
confidence: 91%